2018
DOI: 10.31393/reports-vnmedical-2018-22(1)-19
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of psychoemotional condition of pregnant women-displaced persons

Abstract: One of the most important options of a favorable course of pregnancy, fetal development and physiological delivery is a balanced and preserving psycho-emotional condition of a woman during pregnancy. In order to study peculiarities of psycho-emotional condition of pregnant women-displaced people, dynamic prospective examination of 96 pregnant women in term of gestation more than 22 weeks (the main group) and 34 pregnant women from the local area (the control group) was conducted. According to STAI data, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
2
8
0
Order By: Relevance
“…Pregnant women who have been forced to relocate within their own country display a high amount of both reactive and personal anxiety. In pregnant women who were internally displaced, reactive anxiety was 3.3 times higher, and personal anxiety was 2.6 times higher than in pregnant women who were not internally displaced (Zhabchenko et al, 2018). However, to date, there are no publications on changes in the mental health of pregnant women and mothers of newborn children during the full-scale war in Ukraine.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Pregnant women who have been forced to relocate within their own country display a high amount of both reactive and personal anxiety. In pregnant women who were internally displaced, reactive anxiety was 3.3 times higher, and personal anxiety was 2.6 times higher than in pregnant women who were not internally displaced (Zhabchenko et al, 2018). However, to date, there are no publications on changes in the mental health of pregnant women and mothers of newborn children during the full-scale war in Ukraine.…”
Section: Introductionmentioning
confidence: 93%
“…The number of women fleeing the country, returning to Ukraine, and remaining in Ukraine even though the ongoing hostilities is difficult to estimate. However, it can be concluded that many Ukrainian women have experienced and will experience stress and/or possible adverse consequences (or trauma) related to the war and forced migration ( Ancheva and Morozova, 2016 ; Zhabchenko et al, 2018 ; Romanenko, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These women exhibited heightened indications of both responsive and personalized anxiety, as well as depressive symptoms, autonomic dysfunction, and sleeplessness [9]. According to the findings of a number of researchers [18], anxious and neurotic states are distinguished by high levels of both personal and reactive anxiety. The responsive anxiety is found to be 3.3 times more prevalent in pregnant women who've been internally displaced compared to pregnant women that weren't internally displaced, and individual anxiety is found to be 2.6 times more prevalent in pregnant women who were internally displaced compared to pregnant women that weren't forcibly displaced.…”
Section: Literature Overviewmentioning
confidence: 99%
“…These women have increased indicators of reactive and personal anxiety, depressive manifestations, the presence of autonomic dysfunction, and insomnia (Romanenko, 2020). According to some authors (Zhabchenko et al, 2018), anxiety and neurotic states characterized by high levels of reactive and personal anxiety. In pregnant internally displaced women, reactive anxiety is 3.3 times higher than in pregnant women who were not internally displaced; personal anxiety in pregnant internally displaced women is 2.6 times higher than in pregnant women who were not internally displaced.…”
Section: How Do the War And Refugee Status Experiences Affect Perinat...mentioning
confidence: 99%